A identificação com o time, a curiosidade específica do torcedor e a satisfação do torcedor como antecedentes da intenção de compra do torcedor de futebol no Brasil - Crosara Junior, Ademar (2016)
This research had as its objective describing how the intention to buy products of their favorite team of the soccer fans in Brazil, as well as the intention to watch its games, are influenced by some of its antecedents, being: the specific interest of the fans, the love for the team, the identification of the fans with the team and the supporter’s satisfaction. There are different reasons that cover the academic and management points of view that justify the development of this research. From the academic point of view, it can be seen that even growing, there are few publications dealing with sports consumer behavior in Brazil, suggesting a gap in the literature regarding this type of study (FAGUNDES et al, 2012). Even elsewhere human behavior has been studied in many domains but interest in the context of sport has not been as well researched (PARK; MAHONY; GREENWELL, 2010; PARK et al., 2008). For management the results will be able to help deepening the knowledge about the supporter, providing information so that the organizations which operate in the sector can develop more assertive marketing strategies to attract and retain the soccer fan in Brazil, both by buying products linked to the team and by watching the matches; the constructs used in this research were: the supporter’s specific interest, the identification with the team, the love for the team and the satisfaction of the supporter. From this scenario, two theoretical models were elaborated, one related to the purchase of products of the team contemplating four hypotheses; and the other connected to the consumption of watching the matches of the favorite team, contemplating another four hypotheses. The method adopted was that of quantitative exploratory research. An electronic survey was used for the data collection. The statistical technique chosen was Structural Equations Modeling (SEM). The number of responses considered valid for the study was 499. The results of the research proved six of the proposed hypotheses. The tests applied in the structural models 1.1 and 1.2 pointed out their adjustments and